Nuclear power technology: an analysis and informed opinions - Zio, Enrico; Shirvan, Koroush; Duffey, Romney B.; D’Auria, Francesco (Frontiers in Nuclear Engineering, 2025)
“We have opinions, we make observations, we change our opinions.” Stephen Senn, Dicing with Death, 2003. The purpose of this review paper is to inform debate and provide snapshot opinions about challenges and solutions for the development of nuclear fission technology. We review the socio-political and techno-economic status of nuclear power technology, which, as almost always during its history, is on an edge from which it may jump to success or fall into the abyss of oblivion. Recent nuclear projects and claims are reviewed in light of lessons learned from the international aircraft and minerals processing industries on manufacturing, construction, and technology maturity. For new nuclear reactor projects and designs, these experiences assist in systematically and objectively quantifying investor risk. We strongly recommend the deployment of nuclear fission for energy production everywhere in the world, depending on the scale and dominant economic factors.